Measuring the Validity and Reliability of Research Instruments. (24th August 2015) - Mohamad, Mimi Mohaffyza; Sulaiman, Nor Lisa; Sern, Lai Chee; Salleh, Kahirol Mohd
Abstract: This paper discussed how the applying of Rasch Model in validity and reliability of research instruments. Three sets of research instruments were developed in this study. The Felder-Solomon Index of Learning Styles (ILS) is essential to find out the learning style abilities of learners. Students' Perception in Cognitive Dimension (SPCD) was developed to identify student perception toward their cognitive abilities, and Students' Cognitive Mastery Achievement Test (CMAT) is used to measure student mastery in a particular subject. The study aims to produce empirical evidence of validity and reliability using the Rasch Model. A small survey was conducted on 28 vocational college students enrolled in the Building Construction course. The ILS consists of four constructs, whereas the SPCD and CMAT validate based on three constructs. The value of reliability was based on Cronbach alpha with appropriate values range. The construct validity was analyzed based on the Rasch model with infit and outfit mean square (MNSQ) value. Three experts in the building construction subject examined the content validity of SPCD and CMAT. Assessor agreement can be calculated as percent-agreement. Percent-agreement statistics can be calculated and explained easily. In summary, Rasch Model is suitable to apply in instrument validation process because the concept of item response theory.